Cross-cultural research methods [ - Ember, Carol R. , 1943-; Ember, Melvin , 1933-2009 (Altamira Press, 2009)
Cross-Cultural Research Methods is an introductory teaching tool that shows students and potential researchers how to describe, compare, and analyze patterns that occur in different cultures.